Ketransitifan dalam Status Facebook: Perspektif Linguistik Fungsional Sistemik - Sugerman Sugerman; Anang Santoso; Sumadi Sumadi (Badan Pengembangan dan Pembinaan Bahasa, 2024)
This study aims to describe the phenomenon of transitivity in Facebook statuses from a functional systemic linguistic perspective by Halliday. The research is of document study nature with a Functional Systemic Linguistics approach. Data was obtained through observation techniques, documentation techniques, and referential matching techniques derived from secondary data, namely Facebook statuses. The findings of this research indicate that clauses whose occurrences dominate over other clauses, such as material processes dominating over verbal, mental, behavioural, and relational processes. Furthermore, clauses that consistently appear in text production processes, such as phenomena, which have dominant occurrences compared to actors, goals, sensers, attributes, and scopes. Additionally, circumstances that dominate over other circumstances in the text include cause, which tends to dominate over matter, role, location, extent, and manner. The implications of this study impact the readers' understanding of the transitivity phenomenon in social media and enrich the literature for the development of discourse courses, critical discourse studies, and linguistics in general. AbstrakPenelitian ini bertujuan untuk mendeskripsikan fenomena ketransitifan dalam status Facebook: perspektif linguistik fungsional sistemik Halliday. Jenis penelitian studi dokumen dengan pendekatan Linguistik Fungsional Sistemik. Data diperoleh melalui teknik observasi, teknik dokumentasi, dan teknik padan referensial yang bersumber dari data sekunder yaitu status Facebook. Temuan penelitian ini menunjukkan bahwa klausa yang kemunculannya mendominasi klausa lain seperti proses material yang mendominasi proses verbal, proses mental, proses perilaku, dan proses relasional. Klausa selanjutnya yang selalu muncul dalam proses pemroduksian teks seperti phenomenon yang kemunculannya dominan dibandingkan dengan actor, goal, senser, attribute, dan scope. Kemudian, sirkumtans yang mendominasi sirkumtans lain dalam teks, yaitu cause yang cenderung mendominasi matter, role, location, extent, dan manner. Implikasi penelitian ini berdampak kepada pemahaman pembaca terhadap fenomena ketransitifan dalam media sosial serta memperkaya literatur untuk pengembangan mata kuliah wacana, studi wacana kritis, dan linguistik secara umum.